Hemostatic therapy in experimental intracerebral hemorrhage associated with the direct thrombin inhibitor dabigatran - Zhou, Wei; Schwarting, Sönke; Illanes, Sergio; Liesz, Arthur; Middelhoff, Moritz; Zorn, Markus; Bendszus, Martin; Heiland, Sabine; Ryn, Joanne van; Veltkamp, Roland (Stroke, 2011)
Background and Purpose: Dabigatran-etexilate (DE) recently has been approved for stroke prevention in atrial fibrillation. However, lack of effective antagonists represents a major concern in the event of intracerebral hemorrhage (ICH). The aims of the present study were to establish a murine model of ICH associated with dabigatran, and to test the efficacy of different hemostatic factors in preventing hematoma growth. - Methods: In C57BL/6 mice receiving DE (4.5 or 9.0 mg/kg), in vivo and in vitro coagulation assays and dabigatran plasma levels were measured repeatedly. Thirty minutes after inducing ICH by striatal collagenase injection, mice received an intravenous injection of saline, prothrombin complex concentrate (PCC; 100 U/kg), murine fresh-frozen plasma (200 μL), or recombinant human factor VIIa (8.0 mg/kg). ICH volume was quantified on brain cryosections 24 hours later. - Results: DE substantially prolonged tail vein bleeding time and ecarin clotting time for 4 hours corresponding to dabigatran plasma levels. Intracerebral hematoma expansion was observed mainly during the first 3 hours on serial T2* MRI. Anticoagulation with high doses of DE increased the hematoma volume significantly. PCC and, less consistently, fresh-frozen plasma prevented excess hematoma expansion caused by DE, whereas recombinant human factor VIIa was ineffective. Prevention of hematoma growth and reversal of tail vein bleeding time by PCC were dose-dependent. - Conclusions: The study provides strong evidence that PCC and, less consistently, fresh-frozen plasma prevent excess intracerebral hematoma expansion in a murine ICH model associated with dabigatran. The efficacy and safety of this strategy must be further evaluated in clinical studies.